Restriction enzyme analysis of satellite DNA components from poultry genome - Sharma, Deepak; Rao, K B C Appa; Rawat, A K (The Indian Journal of Animal Sciences, 2012)
The four economically important species of poultry, viz, chicken (Gallus domesticus), quail (Coturnux japonica), gunea fowl (Numida meleagris) and turkey (Meleagris gallopavo) were studied for both mdividual and comparatIve restriction profile analysis of repetitive DNA using 15 restriction enzymes. Genomic DNA isolated from 10 birds (5 of either sex) from each species were digested satisfactorily with enzymes which include both tetra and hexa cutters. No discrete bands could be observed with any of the enzymes. However, some enzymes (Msp I, Taq I, Apa I, Dra I, Eeo RI, Hind III, Nde I, Pst I and Sac I) yielded few Feeble bands within the smear, No distinct species or sex specific differences were observed with respect to repetitive DNA profile in these poultry species, The results, therefore clearly demonstrated that repetitive DNA component seems to exist moderately and thereby constitute a small proportion to total genome in different poultry species studied.